M-Learning As A Blood Line For Higher Educational Institutions. A Review From Saudi Perspective (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Psychology, information sciences, and sociology, numerous theoretical models have been developed to predict and explain user acceptance of information technology or information systems. M-learning is one of the most pivotal domain of information system technology but it is still in its initial stage in the development of e-learning and distance learning. To deeply understand, the current study aimed to review it from both theoretical and practical point of view to understand the factors inhabiting m-learning in Saudi educational institutions. Various databases such as Elsevier, Springer, Pearson Wiley, Taylor & Francis, Mc Graw- HillYell University, Oxford University, Harvard University were explored to assess the published work of previous studies. In addition, to relate the review with the context of Saudi Arabia, reports from the official institutions were also examined to collect information. The review summarizes the definition, advantages, disadvantages, barriers and current implementations strategies of m-learning in Saudi Arabia. The current study contributes to the body of knowledge by providing the review of the factors that may influence the implementation of m-learning in Saudi Arabia. To the best of current study’s author knowledge, no such research has been conducted before.